Pendidikan Kesehatan Kepada Ibu dengan Anak Pneumonia terhadap Pengetahuan Sikap dan Konatif Ibu Tentang Vaksinasi PCV (Journal of Telenursing (JOTING), 2025)
This study aims to determine the relationship between knowledge, attitudes and conative mothers with children with pneumonia about PCV vaccine in a primary health care service in Pontianak city. This study was conducted at a private clinic in Pontianak city, using a quantitative research approach. This study used a pre-experimental design, involving 70 respondents mothers with children under 5 years old. The instrument used a questionnaire and the data collected, then tested statistically using the Wilcoxon test. The results of the study, the majority of respondents had a high school education background (31.4%), followed by elementary school (32.9%) and junior high school (25.7%). Only a few had a bachelor's degree (8.6%) and D3 (1.4%). This shows that the level of education of respondents tends to be low to medium, which can affect their understanding of PCV vaccination before being given counseling. Conclusion, Counseling through seminars has proven to be an effective method to increase awareness and acceptance of PCV vaccination among mothers with children with pneumonia Keywords: Pneumonia, attitude, knowledge, conative, PCV vaccine